A case example of one state's efforts to measure and address the critical shortage of school psychologists. Issue 10 (13th September 2019) - Mann, Angela; Castillo, Jose; Myers, Mary Alice
Abstract: Despite persistent calls for school psychologists to provide comprehensive and integrated services, school psychologists may have difficulty providing these services because of critical shortages in the profession. This practical action research study involved surveying district supervisors of school psychologists and training program directors in the state to identify the current and projected shortages in Florida. This multimethod, multi‐informant case example also focused on facilitators of and barriers to addressing the critical shortage. How the data have been used to inform recruitment, retention, and advocacy efforts to identify school psychology as a critical shortage legislatively are provided as well as recommendations for future research.